Motivação dos professores no novo ensino médio: estudo de caso em Manaus à luz da teoria dos dois fatores - Lopes, Antônio Jorge Rodrigues Monteiro (Brasil, 2024)
This article evaluates teachers' motivation in the context of the New High School, established by Law No. 13,415/2017, which aims to reformulate secondary education in Brazil, offering students the possibility of opting for professional and technical training within the teaching hours regular. At the end of the three years, students must be certified in both secondary education and in the technical or professional course of your choice. The objective of this study is to evaluate the factors that influence the satisfaction and dissatisfaction of teachers in this new model, considering the working conditions, support from the educational department (including logistical and laboratory) and motivational and hygienic factors, based on the Two-Factor Theory of Herzberg. The justification for the study lies in the importance of teachers’ motivation to the success of the implementation of the New Secondary Education and, consequently, for the quality of education offered. The research uses a quantitative approach, with questionnaires semi-structured studies applied to teachers at the Maria Rodrigues Tapajós State School, to explore the factors of satisfaction and dissatisfaction. The results indicate that 75% of teachers feel unmotivated due to hygiene factors, such as low pay and lack of infrastructure, while a smaller portion finds motivation in interacting with students and in pedagogical autonomy. It is concluded that, for the New Secondary Education to be effective, it is essential improve teachers’ working conditions, balancing hygienic and motivational, thus ensuring an educational environment that promotes motivation and teaching commitment.